Navigating multipositionality in ‘insider’ ethnography (Medicine Anthropology Theory, 2017)
In this article, I reflect on my experience of conducting ‘insider’ ethnography in a multidisciplinary collaborative project that evaluates HIV treatment as prevention in Swaziland. Having worked as the project’s social science coordinator for over five years, I discuss balancing my role as an insider on the study team with studying the project as the object of my doctoral research. Drawing on field notes taken during the design and implementation of the project, I discuss how my proximity to the study team created certain expectations in my interactions with team members and clinic staff. In some instances, I distanced myself from the study by not participating or not supporting a consensus option; my doing so engendered a sense that I was being disloyal and sometimes created frustration among my colleagues. The multipositionality that I navigated was a product of social interactions and therefore inherently relational and intersubjective. This article aims to stimulate self-reflective and methodological discussions of how anthropologists engage in global health research and what kind of knowledge and subject positions such collaborations produce.